Trends and Developments in Marketing Management Research: A Bibliometric Analysis of International Publications 2014 - 2024 - Samsibar (P3M Stia Al Gazali Barru and Meraja media, 2026)
[Full Paper] to pdf Copyright (c) 2026 Meraja journal